Gold Nanobipyramid‐Mediated Apoptotic Camouflage of Adipocytes for Obesity Immunotherapy. Issue 8 (25th December 2022) - Yan, Jiao; Wang, Yanjing; Mu, Zhengzhi; Han, Xiaoqing; Bi, Luopeng; Wang, Xingbo; Song, Panpan; Kang, Yaqing; Wang, Lulu; Zhang, Xueyan; Wang, Yanbo; Zhang, Haiyuan
Abstract: Obesity treatment is a global public health challenge due to inadequate weight loss and weight regain even after endeavors with multimodal treatments. Considering the abundance of resident macrophages in adipose tissues, precise regulation of the interactions between macrophages and adipocytes may provide chances for immunotherapy of obesity. Herein, inspired by the phagocytosis of macrophages to clear apoptotic cells in homeostasis, an immunotherapy strategy for obesity treatment is proposed for the first time through apoptotic camouflage of adipocytes by PA Au BPs to activate macrophages for clearance, where PA Au BPs are gold nanobipyramids engineered with adipose‐targeting and apoptotic cell‐mimicking functions. During clearance, the macrophage is switched from pro‐inflammatory M1 to anti‐inflammatory M2, remarkably modulating the immune microenvironment of adipose tissues to prevent weight regain. After inguinal injection with PA Au BPs, the body weights of obese mice are effectively decreased by 24.4% and can be decreased by 33.3% when combined with photothermal lipolysis, and little weight regain is associated with these treatments. This study demonstrates that the strategy of camouflaging adipocytes with apoptotic features holds great potential for obesity immunotherapy. Abstract : Inspired by the clearance of apoptotic cells by macrophages, an immunotherapy for obesity treatment is developed for the first time to activate macrophages resident in adipose tissue to clear adipocytes by camouflaging adipocytes with apoptotic features by gold nanobipyramids, which not only induce significant weight loss but also prevent weight regain, holding great potential for clinical translation.